The ideas-informed society : why we need it and how to make it happen - Brown, Chris; Handscomb, Graham (Emerald Publishing Limited, 2023)
Democratic societies thrive when citizens actively and critically engage with new ideas, developments and claims to truth. Not only can such practices result in more effective choice-making, but they can also lead to widespread support for progressive beliefs, such as social justice. With Western societies in the midst of environmental, social and political crises, it seems more pertinent than ever that citizens become "ideas-informed'. Presenting concepts from academia, industry, and practice, The Ideas-Informed Society closes the gap between the ideal of the ideas-informed society and the current reality. By exploring what it means to be ideas-informed and the benefits for both individuals and society, the chapters conceive what an ideal ideas-informed society would look like, what are the key ingredients of an ideas-informed society, and how to make it happen.
Keywords: Social psychology.; Idea (Philosophy); Communication -- Social aspects.; Psychology -- Social Psychology.; Social, group or collective psychology.; elektronické knihy; electronic books